Augustus De Morgan, Polymath (Open Book Publishers, 2024)
When Augustus De Morgan died in 1871, he was described as ‘one of the profoundest mathematicians in the United Kingdom’ and even as ‘the greatest of our mathematicians’. But he was far more than just a mathematician. Because much of his voluminous written output on various subjects was scattered throughout journals and encyclopaedias, the breadth of his interests and contributions has been underappreciated by historians. Now, renewed interest in De Morgan’s life and work has coincided with the digitization of his extensive library, revealing the extent to which he pioneered and influenced the development of not merely mathematics but also logic, astronomy, the history of mathematics, education, and bibliography. This edited collection celebrates De Morgan as a polymath. Drawing together multiple elements of his activity from a range of publications and archives, its contributors re-assess his academic work, his place in his intellectual environment, and his legacy. The result offers new insight into De Morgan himself as well as the wider circles in which he moved, including his family life.